EZ-fold: an innovative laundry companion / Miqdad Khairulmaini ... [et al.] - Khairulmaini, Miqdad; Aini, Ahmad Zikry; Ramlan, Abdul Rahman; Norazlan, Muhammad Azarul Naim; Mohd Yunus, Mohamad Nurammar Adha (2020)
The increase presence of all-day laundry outlets has help people with busy working schedules to do their laundry at any given time throughout the day. Besides washing, these laundry outlets also provide dryers allowing people to dry their washed clothes. However, these laundry outlets still lack a crucial component that makes doing laundry a complete chore which is clothe folding. Therefore, the main objective of this project is to produce a prototype for a cloth folding machine which can be used to complement the laundry processes of washing and drying at the laundry outlets. The methods used to achieve the objective includes designing the product, fabricating the product, and programming the relevant software for the folding operation. Findings showed that not only can the product help to fold clothes automatically, it also helps reduce the amount of time normally taken when compared to manual folding and using conventional folding board. Less human energy is used during folding clothes because to operate this product, it only requires the push of a button to produce a complete fold. The increase in efficiency and ease of operation during the folding process while doing laundry makes EZ-Fold a product with vast potential for commercialization.